2006
DOI: 10.1111/j.1750-3639.2006.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

CD45 Isoform Expression in Microglia and Inflammatory Cells in HIV‐1 Encephalitis

Abstract: CD45 is a membrane tyrosine phosphatase that modulates the function of the hematopoietic cells. In vitro, agonist antibodies to CD45RO or CD45RB isoforms have been shown to suppress microglial activation, but whether microglia in vivo express these isoforms in HIV encephalitis (HIVE) is unknown. Brain sections from control and HIVE were immunostained for CD45 isoforms using exon-specific antibodies (RA, RB, RC and RO). RA and RC were limited to rare lymphocytes, while RB expression was robust in microglia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 61 publications
2
24
1
Order By: Relevance
“…The presence of macrophages and lymphocytes in the active MS lesion was established in several studies [7,25] and immunostaining for CD68 and CD45 to highlight such inflammatory cells in brain tissue was previously reported [10]. However, the present study revealed that both CD68 and CD45 showed no detectable inflammatory response in the JVL group.…”
contrasting
confidence: 55%
“…The presence of macrophages and lymphocytes in the active MS lesion was established in several studies [7,25] and immunostaining for CD68 and CD45 to highlight such inflammatory cells in brain tissue was previously reported [10]. However, the present study revealed that both CD68 and CD45 showed no detectable inflammatory response in the JVL group.…”
contrasting
confidence: 55%
“…Mice were reconstituted with human peripheral blood lymphocytes; the leukocyte common antigen CD45 is abundantly expressed in human lymphocytes, and HIV infection is often associated with increased infiltration of leukocytes into the CNS, including T lymphocytes. 43,44 Our study showed equal infiltration of human T lymphocytes into the CNS of untreated and nanoART-treated infected mice, indicating that the observed differences in viral gene expression are not due to differences in the numbers of human lymphocytes in the brain. NanoART treatment of infected mice was also associated with significantly decreased brain CD11b RNA levels.…”
Section: Discussionmentioning
confidence: 86%
“…We also analyzed CD45, a common leukocyte antigen expressed on all leukocytes. Ramified parenchymal microglia express lower levels of CD45 than peripheral macrophages (26,27), while the expression of CD45 in microglia may be increased under certain pathological conditions such as HIV encephalitis (28,29) and Alzheimer's disease (30). For the study here, expression of CD45 was clearly more upregulated in CD14 Ϫ/Ϫ mice than in WT mice at 90 and 120 dpi (Fig.…”
Section: Cd14mentioning
confidence: 82%